2018
DOI: 10.1007/s10439-018-2003-0
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Scalp in Head Impact Kinematics

Abstract: The best way to reduce the risk of head injury (up to 69% reduction) is to wear a helmet. In recent years, the improvement of helmet standard tests focused on reproducing realistic impact conditions and including the effect of rotational acceleration. However, less importance has been given to the development of a realistic headform. The goal of this work was to evaluate the role of scalp tissue in head impact kinematics; both with respect to its mechanical properties and with respect to its sliding properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 28 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…Current study limitations include: firstly, the subject-specific material properties have to be validated with additional dynamic experiments which can be reconstructed with FE simulations to refine the parameter selection and allow [48]. They reported that the scalp is an important factor in impact kinematics [49,50]. Finally, the robustness of the statistical analysis in this study is hampered by the limited number of data points available for the frontal and occipital impacts.…”
Section: Study Limitations and Future Workmentioning
confidence: 99%
“…Current study limitations include: firstly, the subject-specific material properties have to be validated with additional dynamic experiments which can be reconstructed with FE simulations to refine the parameter selection and allow [48]. They reported that the scalp is an important factor in impact kinematics [49,50]. Finally, the robustness of the statistical analysis in this study is hampered by the limited number of data points available for the frontal and occipital impacts.…”
Section: Study Limitations and Future Workmentioning
confidence: 99%
“…Several biomedical applications require knowledge of the mechanical behaviour of the scalp, including skin grafting, skin expansion [7][8][9] and head impact biomechanics [10][11][12][13][14][15]. Indeed, the scalp was previously found to substantially affect head kinematics and impact energy during helmet testing [11,16]. From a mechanical point of view, the scalp is a complex tissue; it exhibits a non-linear stress-strain relationship, anisotropy and its mechanical properties depend on strain rate.…”
Section: Introductionmentioning
confidence: 99%
“…Medical literature shows a variety of tolerance limits of the skin [3,6,7,[14][15][16][17] and cranial bones [2,10,11,18]. The sometimes high differences in reported fracture thresholds are presumably the consequence of the variability of the used measuring/testing methods and conditions.…”
Section: Discussionmentioning
confidence: 99%